2012
DOI: 10.1186/1297-9716-43-63
|View full text |Cite
|
Sign up to set email alerts
|

A relevant long-term impact of the circulation of a potentially contaminated vaccine on the distribution of scrapie in Italy. Results from a retrospective cohort study

Abstract: A sudden increase in the incidence of scrapie in Italy in 1997 was subsequently linked to the use of a potentially infected vaccine against contagious agalactia. The relative risk for the exposed farms ranged between 6 and 40. The aim of this study was to assess the long-term impact of exposure to the potentially scrapie-contaminated vaccine on the Italian classical scrapie epidemic. We carried out a retrospective cohort study, fitting mixed-effects Poisson regression models, dividing national geographic areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…Highfrequencies were detected in Aspromontana (10.3%) and Cilentana (18.2%) similar to the previously described Sicilian goats (Girgentana and Rossa Mediterranea in Table 1) in which a direct relation of its high prevalence with the high-scrapie incidence has been postulated (Migliore et al 2017). In Italy, northern breeds showed low-frequencies of K222 (Acutis et al 2008) but also a lower incidence of scrapie as reported in Bertolini et al (2012). As shown in Figure 3, Aspromontana and Cilentana are both reared in provinces with an incidence of the disease between 0.2 and 0.84.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Highfrequencies were detected in Aspromontana (10.3%) and Cilentana (18.2%) similar to the previously described Sicilian goats (Girgentana and Rossa Mediterranea in Table 1) in which a direct relation of its high prevalence with the high-scrapie incidence has been postulated (Migliore et al 2017). In Italy, northern breeds showed low-frequencies of K222 (Acutis et al 2008) but also a lower incidence of scrapie as reported in Bertolini et al (2012). As shown in Figure 3, Aspromontana and Cilentana are both reared in provinces with an incidence of the disease between 0.2 and 0.84.…”
Section: Discussionsupporting
confidence: 81%
“…The South Italian breeds showed six polymorphisms and both confirmed a high-level of the allele resistant K222 as previously observed for the Sicilian goats (Migliore et al 2015;Vitale et al 2016) where a relation with high-scrapie incidence has been postulated (Migliore et al 2017). Scrapie incidence is higher in South and Central Italy compared to the northern regions and the highest incidence has been observed in some provinces of Sicily, Sardinia and Central Italy probably related to the usage of a contaminated vaccine as shown in Figure 3 (Bertolini et al 2012). Highfrequencies were detected in Aspromontana (10.3%) and Cilentana (18.2%) similar to the previously described Sicilian goats (Girgentana and Rossa Mediterranea in Table 1) in which a direct relation of its high prevalence with the high-scrapie incidence has been postulated (Migliore et al 2017).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The administration of this vaccine was identified as the cause of scrapie outbreaks in a number of flocks (Gordon, 1946). More recently, in Italy, several hundred CS cases were observed in sheep and goats that had been vaccinated against Mycoplasma agalactiae with a vaccine produced using homogenised, filtered ovine brains, mammary glands and lymph nodes (Capucchio et al, 1998): recently a cohort study confirmed the impact of this iatrogenic transmission on the spread of CS in Italy (Bertolini et al, 2012).…”
Section: Epidemiologymentioning
confidence: 99%
“…There has been no evidence so far of the possible transmission of either classical or atypical scrapie from animal to animal by using pituitary-derived hormones. However, transplantation, implantation and inoculation of infective body tissues and their products have been shown to transmit TSEs in a number of different species (Gordon, 1946, Brown and others 1999, Verdrager 1999, Bertolini and others 2012) and there is evidence that scrapie has been transmitted through vaccination for other diseases (Gordon 1946, Bertolini and others 2012). In fact, the pituitary-derived hormone route of transmission may have been overlooked in classical scrapie because of the high transmissibility of the disease, while it may have constituted the only route of introduction into the flock for atypical scrapie.…”
mentioning
confidence: 99%